Econometric Modelling of the Sterling Effective Exchange Rate - Davidson, James E. H. (Review of Economic Studies, 1985)
The exchange rate is recognised as a particularly tricky subject for modelling and prediction. The problems of unobservables such as expectations, of simultaneity, and of policy changes (both overt and covert) in the sample period to which models must be fitted may account for the disappointing results of recent attempts to test theories of exchange rate determination. This paper develops an appropriate empirical model to deal with these problems; it allows consideration of the proper interpretation of theoretical assumptions and determination of how far modelling for ex ante prediction can succeed.